Inside the shadows: a survey of UK human source intelligence (HUMINT) practitioners, examining their considerations when handling a covert human intelligence source (CHIS). Issue 4 (4th July 2022) - Moffett, Lee; Oxburgh, Gavin E.; Dresser, Paul; Watson, Steven J.; Gabbert, Fiona
Abstract : Law enforcement agencies in the UK are embracing evidence-based policing and recognise the importance of human source intelligence (HUMINT) in the decision-making process. A review of the literature identified six categories likely to impact the handling of a covert human intelligence source (CHIS) or an informant: (a) handler personality traits; (b) informant motivation; (c) rapport; (d) gaining cooperation; (e) obtaining information, and (f) detecting deception. This study sought to identify which of these categories current HUMINT practitioners considered the most when planning and conducting a meeting with an informant. A bespoke online survey was designed and disseminated to 34 practitioners using purposive and snowball sampling. Directed content analysis and thematic content analysis were conducted. Results indicate that practitioners appear most concerned with gaining co-operation (d) and detecting deception (f). Results also found an inter-connectivity between the six categories, with informant handlers often having to balance competing requirements. Implications for future research are discussed.